Gender dimension of technology adoption: the case of technologies transferred in Ghana. Issue 4 (19th May 2022) - Quaye, Wilhelmina; Onumah, Justina Adwoa; Boimah, Mavis; Mohammed, Abubakari
ABSTRACT: The paper sought to examine factors affecting the level of adoption of technologies transferred to farmers in the Modernisation of Agriculture in Ghana Project (MAG) from gender and power relations perspectives. Results of the study indicate a high rate of adoption of rice and maize technologies by both male and female farmers. Factors influencing adoption include extension service delivery, membership in farmer-based organisation (FBOs), and age. The likelihood of adoption of technologies increased with being a female farmer compared to being a male farmer. There was a discriminatory access to production resources such as land and tractor services against female farmers.